2022
DOI: 10.1155/2022/9999343
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MBNL1-AS1 Represses Proliferation and Cancer Stem-Like Properties of Breast Cancer through MBNL1-AS1/ZFP36/CENPA Axis

Abstract: Background. Emerging studies have revealed long noncoding RNAs (lncRNAs) were key regulators of cancer progression. In this research, the expression and roles of MBNL1-AS1 were explored in breast cancer (BC). Methods. In this study, the MBNL1-AS1 expression in breast cancer tissue, as well as in cell line, was studied by qRT-PCR assays. The effects of MBNL1-AS1 on proliferation and stemness were evaluated by MTT assays, colony formation assays, orthotopic breast tumor mice models, extreme limiting dilution ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…An integrated expression profiling analysis identified that high CENPA level in triple-negative breast cancer was correlated with poor prognosis, thereby suggesting its potential clinical therapeutic applications [34]. In addition, a recent study revealed the upstream regulatory genes of CENPA, which suggested that lncRNA MBNL1-AS1/ MBNL1-AS1/ZFP36 axis suppressed proliferation and cancer stem-like properties of breast cancer cells through reducing CENPA mRNA stability [35]. Given the momentous roles of CENPA in breast cancer, our study investigated the accurate functions and downstream pathways of CENPA in breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…An integrated expression profiling analysis identified that high CENPA level in triple-negative breast cancer was correlated with poor prognosis, thereby suggesting its potential clinical therapeutic applications [34]. In addition, a recent study revealed the upstream regulatory genes of CENPA, which suggested that lncRNA MBNL1-AS1/ MBNL1-AS1/ZFP36 axis suppressed proliferation and cancer stem-like properties of breast cancer cells through reducing CENPA mRNA stability [35]. Given the momentous roles of CENPA in breast cancer, our study investigated the accurate functions and downstream pathways of CENPA in breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…More mechanisms are still under exploration. Other genes predicted to be the targets of miR-223-3p from database have also been found to have some anti-tumor effects, such as FAT1, whose significantly decrease has been reported to be associated with poor prognosis and invasiveness in invasive ductal carcinoma [35] ; MBNL1 is demonstrated to be significantly downregulated in breast and gastric cancers in several studies, and MBNL1 can interact directly with ZFP36 to downregulate CENPA, thereby inhibiting the proliferation and stemness of breast cancer cells [ 36 , 37 ]. CBFB, together with its binding partner RUNX1, regulates multiple signaling pathways, and breast cancer cells may evade both translational and transcriptional surveillance simultaneously caused by CBFB downregulation [38] .…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies were permitted by the Joint Ethics Committee of the Harbin Medical University Health Authority (Harbin, China). 37 T47D cell lines expressing luciferase were used for in vivo experiments. Female NOD/SCID mice (Vital Rivers, China) were housed in a specific pathogen‐free barrier facility with a 12‐h light/12‐h dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Animal studies were permitted by the Joint Ethics Committee of the Harbin Medical University Health Authority (Harbin, China) 37. T47D cell lines expressing luciferase were used for in vivo experiments.…”
mentioning
confidence: 99%